Effectiveness of Tuberculosis Surveillance System in Remote Areas Through A Mixed-Methods Approach: A Case Study in Kabawo District, Muna Regency - Tri Rahmatiani Gani; Windy Mariane Virenia Wariki; Grace Debbie Kandou (International Journal of Health and Pharmaceutical (IJHP), 2026)
Tuberculosis (TB) remains a public health problem, especially in remote areas with limited resources and access to health services. The effectiveness of the TB surveillance system is crucial for successful disease control. This study aimed to assess the effectiveness of the TB surveillance system in Kabawo District, Muna Regency, using a mixed-methods approach. This study employed a mixed-methods design with a concurrent triangulation strategy. Quantitative data were analyzed univariately using SPSS to assess the components of the surveillance system, while qualitative data were obtained through in-depth interviews and analyzed descriptively. The quantitative analysis showed that the availability and capacity of human resources had an average score of 3.28, the TB case reporting system 3.83, the TB treatment success process 3.52, and the availability of facilities and infrastructure 2.89. The TB case detection process had an average score of 0.87. The overall effectiveness of the TB surveillance system was categorized as effective with an average score of 0.85. Qualitative findings revealed barriers such as social stigma, trust in traditional medicine, and limited geographic access that impacted the implementation of TB surveillance. The TB surveillance system in Kabawo District is considered effective, but still requires strengthening in the aspects of active case detection, utilization of facilities and infrastructure, as well as socio-cultural and geographic access-based interventions to increase effectiveness in a sustainable manner.